A molecular approach combined with American Thyroid Association classification better stratifies recurrence risk of classic histology papillary thyroid cancer. (14th December 2018) - Lin, Alexander J.; Samson, Pamela; DeWees, Todd; Henke, Lauren; Baranski, Thomas; Schwarz, Julie; Pfeifer, John; Grigsby, Perry; Markovina, Stephanie
Abstract: Background: Prognosis among patients with differentiated thyroid cancer is widely variable. Better understanding of biologic subtypes is necessary to stratify patients and improve outcomes. Methods: In patients diagnosed with classic histology papillary thyroid cancer treated from 1973 to 2009, BRAF V600E mutation status was determined on surgical tumor specimens by restriction fragment length polymorphism analysis. A tissue microarray (TMA) was constructed from tumor specimens in triplicate and stained by immunohistochemistry for RET, phospho‐MEK, MAPK(dpERK), PPARγ, and phospho‐AKT(pAKT). Stained slides were scored independently and blindly by two investigators and compared to tumor and patient characteristics and outcomes. Results: A total of 231 patients had archived formalin‐fixed, paraffin‐embedded tumor tissue available and were included on the TMA. Mean age at diagnosis was 44 years (range 6‐82 years); proportion of patients with female sex was (72%); 2015 American Thyroid Association (ATA) risk stratification was low (26%), intermediate (32%), and high (42%). BRAF V600E mutation was found in 74% of specimens, and IHC was scored as positive for RET (61%), MAPK (dpERK) (14%), PPARγ (27%), and pAKT (39%). Positive RET staining was associated with a lower risk of recurrence (HR = 0.46, 95% CI 0.22‐0.96). No other molecular biomarkers were independent predictors of recurrence on univariable analysis. On RPA, patients with RET‐negative and either MAPK(dpERK)‐positive or pAKT‐positive tumors were identified to have a high risk of recurrence (HR = 5.4, 95%CI 2.5‐11.7). This profile remained associated with recurrence in a multivariable model including ATA risk stratification (HR = 2.8, 95% CI 1.3‐6.0). Conclusion: Characterization of molecular pathways involved in cPTC tumorigenesis may add further risk stratification for recurrence beyond the 2015 ATA risk categories alone. Abstract : Tumor cell protein expression of molecular factors along the BRAF/MAPK (dpERK) and PI3K/pAKT tumorigenesis pathways was found to be variable in 231 patients with classic papillary thyroid cancer. A molecular high‐risk profile characterized by negative RET staining and either positive MAPK (dpERK) or pAKT was independently associated with cPTC recurrence and further stratified patients for recurrence and death in the American Thyroid Association risk groups.